Use of Outcrop as Substitute for Subsurface Shale: Current Understanding of Similarities, Discrepancies, and Associated Challenges - Sharifigaliuk, H.; Mahmood, S.M.; Ahmad, M.; Rezaee, Reza (2021)
Full coring in shale reservoirs is challenging, time consuming, and risky due to fragility. Therefore, shale outcrop analogs are often used as an alternative to enhance the understanding of corresponding subsurface reservoir formation multifaceted mineralogy and rock characteristics. As consequence, many researchers perform their fundamental experimental studies on the core samples collected from outcrops when the subsurface unconventional shale samples are scarce. An assumption is often made that the rock composition and properties of outcrop and subsurface samples remain the same which raises some serious concerns and demands a thorough review of published research to check the validity of this approach to characterize shale reservoirs. The high degree of lateral and vertical heterogeneity and anisotropy, weathering, contamination, and postdepositional tectonic activities further add to the major challenges. In this literature-based study, the authors revisit the current understanding and challenges of using shale outcrops to complement the available subsurface samples and use them for the preliminary evaluation of underexploration and undeveloped unconventional shale reservoirs. The similarities and discrepancies of mineralogical, petrophysical, geochemical, and geomechanical properties are discussed. Finally, some concluding remarks and recommendations are presented.